Arthrogryposis multiplex congenita with maxillofacial involvement: a case report - Stefano Cirillo; Daniele Regge; Umberto Garagiola; Alessandro Tortarolo; Giuseppe Carlo Iorio; Orges Spahiu; Maria Grazia Piancino (SpringerOpen, 2023)
Abstract Background Arthrogryposis multiplex congenita is a rare condition that mainly involves the lower limbs, characterized by severe joint deformity and contracture, muscular atrophy, and functional impairment. Its clinical manifestations are heterogenous and may involve the maxillofacial district as well. Case presentation This case report describes a 20-year-old patient with arthrogryposis multiplex congenita with skeletal crossbite, facial asymmetry, reduced mouth opening and absence of lateral mandibular movement on the left side. After clinical evaluation, the following exams were required: postero-anterior cephalometric tracing, head and neck electromyography, computerized axiography, computed tomography scan, and maxillofacial magnetic resonance imaging. Orthognathodontic evaluation indicated skeletal asymmetry, reduced condylar movements on the left side and abnormally low electromyography activity of the masticatory muscles on the left side. Computed tomography and magnetic resonance imaging revealed unilateral left mandibular hypoplasia, hypotrophy, and fatty infiltration of masticatory muscles on the left side, as well as immobility of the left condyle during mouth opening, and hypoplasia of the left articular disk, which was however not displaced. Surgery was not indicated and conservative orthognathodontic treatment with function generating bite was suggested to balance the occlusal plane, as well as stretching exercises. Conclusions A rare case of arthrogryposis multiplex congenita with maxillofacial involvement illustrates that a patient-centred, multidisciplinary approach with accurate diagnosis is required to formulate the best treatment plan. Because of the considerable damage to the masticatory muscles, conservative orthognathodontic therapy may be the best treatment option.